Conceptual Model of Determining Factors of Islamic Banking Financial Performance - Sari, Arum Cahaya; Bahri, Efri Syamsul (Yayasan Mitra Peduli Indonesia, 2024)
This study aims to identify the determinants of the financial performance of Islamic banking and develop a conceptual model. This type of research uses a qualitative method with a literature study approach. Data collection uses the publish or perish application selected with the preferred reporting items for the systematic reviews and meta-analyses (PRISMA) approach. This study has identified 46 journals that meet the inclusion and exclusion criteria. Based on the analysis of 46 journals found, 40 determinants of the financial performance of Islamic banking. The financial performance elements of Islamic banking have been compiled in the form of a conceptual model categorized into two dimensions: financial factors and non-financial factors. Furthermore, nine theories are found in 46 journals: agency theory, commercial loan theory, legitimacy theory, exchange theory, company theory, resource-based theory, resource dependency theory, signal theory, and stakeholder theory.